1977
DOI: 10.1083/jcb.74.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Organization of cell junctions in the peritoneal mesothelium

Abstract: Intercellular junctions in the mesothelium of the visceral (mesentery and omenturn), and parietal (diaphragm, pre-aortic, and iliac region) peritoneum were examined in rats and mice by using freeze-cleaved preparations. In addition to usual intercellular junctions (cell body junctions), special junctions are found between cell processes and the surface of the neighboring cell (cell process junctions). Cell body junctions are provided with tight junctions and communicating (gap) junctions. The former consist of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
3

Year Published

1978
1978
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(34 citation statements)
references
References 37 publications
3
28
0
3
Order By: Relevance
“…Perhaps, this kind of tight junction formation process is a general phenomenon in mammalian epithelial cell development. As has been noted previously by other authors [Simionescu and Simionescu, 1977;Okamoto and Ishimura. 1978;Yan cey cr al., 1979;Minutli et al.…”
Section: Discussionsupporting
confidence: 74%
“…Perhaps, this kind of tight junction formation process is a general phenomenon in mammalian epithelial cell development. As has been noted previously by other authors [Simionescu and Simionescu, 1977;Okamoto and Ishimura. 1978;Yan cey cr al., 1979;Minutli et al.…”
Section: Discussionsupporting
confidence: 74%
“…A typical zonula occludens in the epithelium encircles the cytoplasm containing abundant felt work of cytoskeletal elements just beneath the cell apex bearing microvilli. Maculae occludentes on peritoneal mesothelial cells (SIMIoNEscu and SIMIoNEscu, 1977) and chorionic trophoblasts (BARTELS and WANG, 1983) are present on the lateral cell membrane near the microvillous free surface.…”
Section: Discussionmentioning
confidence: 99%
“…As in a previous report (KATAOKA et al, 1982), we prefer the term, macula occludens, to distinguish it from the zonula occludens, the typical belt-like tight junction in the epithelium. In addition to the pancreatic islet cells (ORCi and PERRELET, 1977;KATAOKA et al, 1982), the presence of the macula occludens has been reported on adrenocortical cells (FRIEND and GILULA, 1972), peritoneal mesothelial cells (SIMIONESCu and SIMIONESCU, 1977), renomedullary interstitial cells (MAJACK and LARSEN, 1980), neuroepithelial cells during amphibian neurulation (DECKER and FRIEND, 1974), developing thyroid cells in the chick embryo (ISHIMURA and FUJITA, 1979), chorionic trophoblasts (BARTELS and WANG, 1983) and in the pancreatic acinar cell tumor (IwANIJ et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…There will be no increase in permeability without the rearrangement of the tight junctional complex, located most apically in all endothelial cells and in some parts of the vascular tree (arteries and capillaries); in some specific vascular beds (brain, testis), tight junctional complexes can be found in more than one location along the inter-endothelial space. 53,[96][97][98] Endothelial participation and the mechanisms involved in exacerbated vascular permeability in ALI have been extensively reviewed. 84,94 In pathological conditions, dysfunctional endothelial cells show impaired caveolae and clathrincoated vesicle endocytosis and altered intracellular trafficking and signaling of cell surface receptors such as transforming growth factor beta receptor (TGFβR) and bone morphogenetic protein receptor-2 (BMPR2), both implicated in the pathogenesis of ALI/ARDS.…”
Section: Endothelial Cells and Alimentioning
confidence: 99%